Near-zero-shrinkage Al2O3 ceramic foams with coral-like and hollow-sphere structures via selective laser sintering and reaction bonding. Issue 16 (December 2021) - Dong, Ye; Jiang, Hongyi; Chen, Annan; Yang, Ting; Gao, Shuai; Liu, Shuning
Highlights: Near-zero-shrinkage, high-porosity, and high-strength Al2 O3 ceramic foams were prepared via the SLS/RB process. The ceramic foams consist of coral-like and hollow-sphere structures derived from the raw Al2 O3 /Al composite powders. The effect of raw material composition and Al content on the properties of prepared samples was investigated. The mechanisms of eliminating shrinkage, improving porosity, and enhancing strength were elucidated. Compared with those via other methods, the properties of the Al2 O3 ceramic foams via the SLS/RB process were inspiring. Abstract: The large shrinkage that ceramics undergo during sintering is a severe challenge for high-performance porous ceramics. In this study, we report a powder-based selective laser sintering (SLS) approach to prepare Al2 O3 ceramic foams with near-zero shrinkage, high porosity, and outstanding strength. The ceramic foams consist of specific coral-like and hollow-sphere structures derived from the raw Al2 O3 /Al composite powders via reaction bonding (RB). A near-zero shrinkage of 0.91 ± 0.15 % and a high porosity of 73.7 ± 0.2 % can be achieved based on the Kirkendall effect during the oxidation of Al particles. Meanwhile, the reinforced sintering necks and robust bond-bridge connections between hollow-sphere and coral-like structures result in a remarkable bending strength of 7.37 ± 0.37 MPa. This measured strength is more than six times higher than other fabricated samples from spherical Al2 O3 powders, and the comprehensive performance of ceramic foams prepared by this novel SLS/RB strategy is exceptionally remarkable versus that via conventional forming methods.